2020
DOI: 10.21203/rs.3.rs-23876/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term radiographic outcomes and functional evaluation of ulnar shortening osteotomy in patients with ulnar impaction syndrome and reverse oblique sigmoid notch: a retrospective case series study

Abstract: Background: Ulnar shortening osteotomy (USO) is an effective treatment for ulnar impaction syndrome. However, there has been a concern of osteoarthritis (OA) developing at the distal radioulnar joint (DRUJ) if USO is performed on patients with a reverse oblique sigmoid notch. This study aimed to evaluate the radiographic and functional outcomes following USO in patients with a reverse oblique sigmoid notch.Methods: We retrospectively reviewed our patients with a reverse oblique sigmoid notch who underwent USO … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…De Runz et al 5 found that patients with DRUJ osteoarthritis had worse PRWHE scores than patients without, 5 and other studies suggested that the DRUJ morphology affected the outcome. 4,6,7 However, this study did not have radiological data at late follow-up, and DRUJ morphology could not reliably be assessed. Future prospective studies should further investigate predictors for the long-term patient-reported outcome after USO.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…De Runz et al 5 found that patients with DRUJ osteoarthritis had worse PRWHE scores than patients without, 5 and other studies suggested that the DRUJ morphology affected the outcome. 4,6,7 However, this study did not have radiological data at late follow-up, and DRUJ morphology could not reliably be assessed. Future prospective studies should further investigate predictors for the long-term patient-reported outcome after USO.…”
Section: Discussionmentioning
confidence: 93%
“…Ulna shortening osteotomy (USO) is an established treatment option for patients with ulnar impaction syndrome (UIS). [1][2][3] Previous studies reported good results, but mainly focused on radiological outcomes [4][5][6][7] or clinician-reported outcome measures. 4 However, these studies often lacked patientreported outcome measures (PROMs), preoperative measurements, 5 or had a small sample size.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations